CREATIVE PROCESS OF CHILDREN'S DRAWING IN THE PADHANG NJINGGLANG LEARNING COMMUNITY WITH THE HAPPY MEMORY ACTIVATION METHOD - Lisa Sidyawati; Hartono Hartono; Syakir Syakir; Anang Prasetyo (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Education is the leading force in human life, according to Kant's statement that humans can only become human through education. Humanistic education empowers individuals by fostering intellectual, emotional, and spiritual development. Art education, particularly within this community, serves as a tool to balance these aspects, promoting harmonious personality development. The Padhang Njingglang Community, founded by Anang Prasetyo in Tulungagung in 2008, targets children who are often overly reliant on digital technology and exhibit behavioral issues such as a lack of politeness and reduced engagement in traditional play. The role of the Padhang Njingglang Community is essential in addressing behavioral challenges among Generation Alpha children through humanistic art education. The community employs the